Investigated of Zn-1Mg Alloy Using Potentiodynamic Polarization and Weight Loss Methods in Kokubo’s Solution - Arafat, Andril; Din, Muhammad; Lapisa, Remon; Habibie, Farhan; Prayoga, Ongki (INVOTEK: Jurnal Inovasi Vokasional dan Teknologi, 2026)
Zinc alloys are considered as candidates for bioabsorbable implant materials due to their corrosion rates and their outstanding combination of biodegradability and biofunctionality. This study compares the corrosion behavior of Zn-1Mg alloys prepared in as-cast, as-rolled, and as-extruded forms using two main methods: immersion testing (weight loss) in Kokubo’s Simulated Body Fluid at 37 °C for up to 14 days, and potentiodynamic polarization (PDP). Microstructure characterization was performed using SEM/EDS to identify corrosion products after the corrosion test. The weight loss method showed the highest corrosion rate in the as-rolled sample 0.56 mm/year and the lowest in the as-cast sample 0.35 mm/year. In contrast, the potentiodynamic method showed the lowest corrosion rate in the as-extruded sample 0.019 mm/year. These results indicate that the extrusion process produces a refined and uniform grain microstructure, which contributes to improved electrochemical corrosion resistance. Overall, the corrosion rates of all samples were still within the safe daily intake limits of Zn allowed in the human body. It were concluded that mechanically processed Zn-1Mg alloys (rolling for plates and extrusion for pins) are suitable and promising for use as bioabsorbable metals for non-load-bearing applications such as craniofacial implant applications.